Efektivitas dan Akuntabilitas Pengelolaan Dana Zakat BAZNAS Kabupaten Banyumas Berdasarkan PSAK 109” - Eli Susanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to assess the efficiency of zakat fund management and the accountability of the financial reports of BAZNAS Banyumas Regency for the period 2021 to 2024. The method chosen is descriptive quantitative by analyzing financial report documentation for a four-year period. Data were analyzed using efficiency ratios, operational ratios, zakat fund distribution ratios, and an assessment of the suitability of financial report presentation following PSAK 109. The findings of this study indicate that zakat fund management is efficient because the average efficiency ratio is below 30%, which is the ideal limit. In terms of accountability, financial reports have been prepared in accordance with PSAK 109, although there are still some shortcomings in terms of the completeness of financial report records and online information access. Overall, BAZNAS Banyumas has managed zakat funds well, but still needs to improve digital transparency.